Competitiveness Performance Assessment of the Local Government Units in Lanao Del Norte - Philippines - Charlyn, Charlyn (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
The Cities and Municipalities Competitiveness Index (CMCI) survey is conducted annually to assess the competitiveness of cities and municipalities based on different indicators. The survey is done with the assistance of the Regional Competitiveness Committees (RCCs) consisting of the public and private sectors as well as academia. The College of Business Administration and Accountancy (CBAA) now known as the College of Economics, Business, and Accountancy (CEBA) has been the academic partner of DTI-Lanao del Norte in the annual conduct of the CMCI survey by assisting the 22 municipalities of Lanao del Norte. This study was conducted to assess whether the assistance provided by the academic partner of DTI-LDN has been effective and instrumental in the competitiveness performance based on the LGUs score on the different pillars measured using CMCI criteria designed by the National Competitiveness Bureau. Using the test for difference in means, the results show that there is significant improvement in the LGU overall performance and in terms of economic dynamism, government efficiency, and infrastructure. Using panel analysis, economic dynamism of the municipalities of LDN is significantly driven by government efficiency and infrastructure.